2005
DOI: 10.1177/1062860605279474
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Screening, Treatment, and Prevention of Perinatal Infections in the Philadelphia Birth Cohort

Abstract: Certain population groups are at risk for inadequate prenatal care and transmission of perinatal infections. Philadelphia's birth cohort comprises largely at-risk groups and its infant mortality rate is among the nation's highest. This study identifies factors associated with infectious disease screening, treatment, and prevention in Philadelphia. Delivery charts for a probability sample of 550 patients were reviewed. Demographic factors associated with prenatal and delivery care were identified through Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Providers’ adherence in this study was lower than previous studies [ 8 10 ] including one from Indianapolis [ 13 ] (95-98.2%). These studies were published over 15 years ago.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Providers’ adherence in this study was lower than previous studies [ 8 10 ] including one from Indianapolis [ 13 ] (95-98.2%). These studies were published over 15 years ago.…”
Section: Discussioncontrasting
confidence: 85%
“…Studies have also shown that healthcare providers’ adherence to testing guidelines varies significantly from one infectious disease to the other, and that maternal factors such as insurance type and geographical location are factors that contribute to low adherence [ 8 , 9 ]. Several studies have also noted significant differences in providers’ adherence level based on data source [ 8 , 10 14 ]. The use of administrative data such as Medicaid data has shown providers’ adherence to prenatal syphilis testing to be 60% [ 13 ] while studies utilizing clinical records have found higher adherence rate over 80% [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding clearly implies that prenatal testing is a successful screening tool for identifying women with chronic hepatitis B. Other studies, including a nationwide survey of hospitals, have had similar results with prenatal HBsAg test results documented in 92.6% of maternal medical records . It is reassuring to see that universal prenatal HBV testing, which was recommended by USPSTF in 2004, after risk‐based testing was not capturing all women, has become the norm and is now successfully implemented .…”
Section: Discussionmentioning
confidence: 54%
“…This study relied on maternal self-report; our study has as a strength our ability to have objective evidence of GBS status availability. Another investigation of predictors of screening for perinatal infections in 2000–2001 revealed no differences by race/ethnicity or insurance status with regards to universally-recommended screenings for infections such as hepatitis B, syphilis and rubella, but did show some variation by both race/ethnicity and insurance for infections in which recommendations at the time were based on risk factors, such as GBS, hepatitis C and varicella [15]. The authors suggest that the systems of care in which minority and poor women may be enrolled may have different practice standards, reflective of provider and patient awareness, as well as reimbursement rates of insurers.…”
Section: Commentmentioning
confidence: 99%